Evolutionary traditions and corporate law: the effectiveness and development of liquidation duty in China*. Issue 2 (3rd July 2019) - Wei, Chuyi; Zhao, Jingchen; McCormack, Gerard
ABSTRACT: This article argues for updating and reform of the liquidation duty under Chinese corporate law. It adopts an evolutionary perspective on corporate law in the sense of asking whether the corporate laws co-evolve with, and adapt to the changing conditions of a country, rather than whether laws are converging towards a certain 'developed' model. In some jurisdictions, directors have a creditor-regarding duty when the company is insolvent or near insolvency and this duty is intended to constrain 'moral hazard' issues on the part of corporate insiders. In China, such moral hazard issues are mitigated by the liquidation duty. This article argues that while the liquidation duty is relatively effective, it has created unfairness and undermined the value of formal insolvency law. Drawing on the experience of other jurisdictions especially the United Kingdom in relation to wrongful trading law, this article suggests that a wrongful trading remedy and further restructuring measures might be introduced in China.